Case Report: Early Resection of Pheochromocytoma in a Patient With Cardiogenic Shock Due to Pheochromocytoma-Induced Cardiomyopathy With Extracorporeal Life Support - Lyu, Ting; Niu, Jianhua; Liu, Zhihai; Li, Tong (Frontiers in Cardiovascular Medicine, 2022)
Background: Pheochromocytoma-induced cardiomyopathy is a rare but potentially life threatening complication of pheochromocytoma. It mimics the patterns of stress-induced cardiomyopathy. In severe cases, patients can develop refractory cardiogenic shock require mechanical circulatory support. Case presentation: We presented a case of 54-year-old female who developed refractory cardiogenic shock following an elective orthopaedic surgery complicated by cardiac arrest required veno-arterial extracorporeal membrane oxygenation (VA-ECMO) support. After the urgent coronary catheterisation revealed normal coronary artery, further perusing of the aetiology of cardiogenic shock discovered a pheochromocytoma. With a diagnosis of pheochromocytoma-induced cardiomyopathy, while continuing supportive treatment, the patient had accelerated pre-operative adreno-blockade preparation for a total of six days, and subsequently had the tumor removed with VA-ECMO support. The patient recovered well post-operatively, and was off ECMO support and extubated a few days later. Conclusion: The optimal management of pheochromocytoma-induced cardiomyopathy especially for severe cases is still unclear. While some cases will require mechanical circulatory support to allow left ventricular function recovery, our case also showed that it is possible to introduce alpha blockade safely while patient is on VA-ECMO and have pheochromocytoma removed with VA-ECMO support after accelerated pre-operative preparation.